If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -8 + 6 = 6y + -6 + 4 Reorder the terms: -8 + 6 + 4y = 6y + -6 + 4 Combine like terms: -8 + 6 = -2 -2 + 4y = 6y + -6 + 4 Reorder the terms: -2 + 4y = -6 + 4 + 6y Combine like terms: -6 + 4 = -2 -2 + 4y = -2 + 6y Add '2' to each side of the equation. -2 + 2 + 4y = -2 + 2 + 6y Combine like terms: -2 + 2 = 0 0 + 4y = -2 + 2 + 6y 4y = -2 + 2 + 6y Combine like terms: -2 + 2 = 0 4y = 0 + 6y 4y = 6y Solving 4y = 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. 4y + -6y = 6y + -6y Combine like terms: 4y + -6y = -2y -2y = 6y + -6y Combine like terms: 6y + -6y = 0 -2y = 0 Divide each side by '-2'. y = 0 Simplifying y = 0
| 11x+5/2-11=8 | | 9w-18=-24w+48 | | 4g-6-g-4g= | | -26/12+7/12 | | 8(12x+7)=96x-10 | | 8+.5=2.5a | | m-5m-8m-g= | | 1/3x+(x-15)+(x-25)=320 | | 3(x-5)=20+2(5+3x) | | 2.5(d)=30 | | .2x+5x=7x-18 | | 98x-84=14(7x-6) | | 6x+5=6x-10 | | 3k-1=2m | | a=16+25 | | 5+x,x=-5 | | 1/4(7+3g)=-g/-8 | | 3x+6=162 | | n^2+2n-99=0 | | 3x-4+2x-1=40 | | 6(x+3)-2=28 | | 1/10b^3+10/21b^3 | | 12x+93=12x+7 | | -9+x,x=6 | | 2y-11=15 | | 11a=-143 | | -12+-1x=22-12x+1x | | 2x-1=40 | | x+4(x+2)=44 | | (2,4)y=1/2-7 | | ax=4b | | 2ax-6ay+6x-3by= |